Factors Affecting Islamic Bank Customer Satisfaction - Mariyanti, Tatik; Edastama, Primasatria; Shafiai, Muhammad Hakimi Mohd (Pandawan, 2021)
Customer satisfaction is a basic goal of any form of business or company, because customer satisfaction will provide many benefits for the sustainability of the business. Customer satisfaction will emerge influenced by certain factors. This study aims to analyze several factors that can influence customer impressions, tangible aspects, reliability, employee response, social responsibility, product innovation, competence and communication skills in Islamic banking. The research data was collected from customers of several Islamic banks in Jakarta. The data processed by the regression method with the SPSS software. This study shows that of the seven factors that are used as determinants of satisfaction, there are 4 factors that can affect the level of customer satisfaction at Islamic banks, namely tangibles, employee response, product innovation, and communication skills. Furthermore, this research also found that 3 other factors could not affect the level of customer satisfaction, those are competence, social responsibility, and reliability. The factors that influence the two dominant factors are the communication ability factor and the product innovation factor. The results of this study can help Islamic banks to be able to develop more effective and efficient strategies in terms of establishing high levels of customer satisfaction, so as to generate potential customers and higher profits.